Interleukin-1β activates matrix metalloproteinase-2 to alter lacrimal gland myoepithelial cell structure and function - Morokuma, Junji; Gárriz, Angela; Toribio, Danny; Pagni, Sarah; Zoukhri, Driss (Frontiers in Ophthalmology, 2024)
The aim of the present study is to investigate the role of c-Jun N-terminal kinase (JNK) and matrix metalloproteinase-2 (MMP-2) in mediating the effects of interleukin-1β (IL-1β) on the function of lacrimal gland myoepithelial cells (MECs). MECs isolated from an α-smooth muscle actin–green fluorescent protein (SMA-GFP) transgenic mouse were treated with IL-1β alone or in the presence of SP600125, a JNK inhibitor, or ARP100, an MMP-2 inhibitor. The GFP intensity and the cell size/area were measured, and on day 7, the SMA, calponin, and pro-MMP-2 protein levels and the MEC contraction were assessed. At baseline, the control and treated cells showed no differences in GFP intensity or cell size. Starting on day 2 and continuing on days 4 and 7, the GFP intensity and cell size were significantly lower in the IL-1β-treated samples, and these effects were alleviated following inhibition of either JNK or MMP-2. Compared with the control, the levels of SMA and calponin were lower in the IL-1β-treated samples, and both the JNK and MMP-2 inhibitors reversed this trend. The pro-MMP-2 protein level was elevated in the IL-1β-treated samples, and this effect was abolished by the JNK inhibitor. Finally, oxytocin-induced MEC contraction was diminished in the IL-1β-treated samples, and both the JNK and MMP-2 inhibitors reversed this effect. Our data suggest that IL-1β uses the JNK/MMP-2 pathways to alter MEC functions, which might account for the diminished tears associated with aqueous-deficient dry eye disease.